(untitled) (Bangladesh Medical Journal, 2014)
American Diabetic Association (ADA) affirms HbA1c with cut off value of 6.5% as a diagnostic criteria of diabetes mellitus. World Health Organization (WHO) also supports but recommended that a value <6.5% does not exclude diabetes which is diagnosed by glucose test. The aim of this study was to evaluate the diagnostic efficacy of HbA1c in terms of sensitivity, specificity, positive and negative predictive value and accuracy in a selected group of Bangladeshi subjects. This cross-sectional study included 761 adult Bangladeshi subjects of both sex attending the outdoor in a tertiary healthcare center during the period of September 2009 to September 2010. Fasting, postprandial (2 hours after glucose load) plasma glucose and HbA1c were measured. Diabetes is defined according to HbA1c and plasma glucose. Sensitivity, specificity, positive and negative predictive value of HbA1c were 90.00% (CI 86.48-92.86%), 76.21% (CI 71.68-80.35%), 78.17% (CI 73.94-82.00%) and 88.96% (CI 85.10-92.10%) respectively. Accuracy was 82.92% with odds ratio (OR) 28.84 (CI 19.10-43.54%); p < 0.001. Though HbA1c revealed remarkable diagnostic efficacy and ease of performance, still it can not over rule the role of plasma glucose in diagnosis of diabetes mellitus. DOI: http://dx.doi.org/10.3329/bmj.v41i1.18785 Bangladesh Medical Journal 2012 Vol. 41 No. 1; 53-54